Xenotransplantation of caprine pancreatic islets in diabetic mice - Hani, Homayoun (2013)
Diabetes is one of the aggressive metabolic syndromes, which allied with high levels of blood glucose subsequent of imperfections in insulin production that causes glucose to increase in the body. For decades, excellent improvement has been obtained in clinical transplantation of pancreatic islet. Because of that, islet transplantation has become the main alternative cure for type 1 diabetics. However, important obstacles still remain to use of islet transplants routinely as a treatment choice. The deficiency of human islet donors makes the search for alternative islet sources mandatory for future developments in pancreatic islet transplantation. Venturing into xenotransplantation provides tremendous extensive sources of islet cells. The improvement of genetically engineered pigs expressing human complement regulatory proteins to defeat immune damaging pathways has been promising; however, the necessity of massive immunosuppressive and the concern for zoonotic viral transmission are some of the constraints. The present investigation unravels the potential of caprine islets as an alternative islet source for xenotransplantation. One of the main reasons for performing this preliminary study was that religious and cultural factors in countries including Malaysia may favor goats over pigs as xenograft donors. However, potential limitations associated with the use of caprine donors must be recognized. First, the mean yield of 120,000 islets per adult goat is somewhat lower than the reported yield of up to 360,000 islets obtained from adult pigs. Second, the efficacy of goat insulin in humans is not known. The amino acid sequence of goat insulin differs from that of human insulin at four residues, compared to pig insulin which differs at only one. However, bovine insulin, which differs at three of the same four residues as goat insulin, has been shown to control diabetes in humans. Furthermore, should there be a problem with goat insulin, it would be feasible to genetically modify goats to produce human insulin. This study aimed i) to characterize viable caprine islets, ii) to inspect the impact of antioxidant and secretagogues factors in vitro maintenance of caprine islets and their viability in culture media iii) to scrutinize the in vitro enhancing factors for insulin promoter gene and protein expression in caprine islets, iv) to assess the functionality of grafted caprine islets in immunized diabetic murine models. Microscopic characterization of viable caprine islets was carried out to evaluate endocrine cell types. Caprine islets were successfully obtained using a collagenase based digestion, isolation and Euro-Ficoll density gradient purification technique at optimum pH (= 7.4). Purity and viability of islets were determined by dithizone and FDA/PI staining respectively. The viability of purified islet cells exceeded 90%. Caprine islet morphological assessment and cyto-architectural study were carried out using single and multiple immunostaining for insulin, glucagon and somatostatin and then assessed by confocal microscopy and flow cytometry. Under the confocal microscope, the mean percentage of β-cell, α-cell and δ-cell in different layers of purified islet were 38.01 ± 12.47%, 30.33 ± 12.33 and 2.15 ± 1.17%, respectively. Majority of β-cells were centralized whilst the other two cell types were placed in the peripheral regions. A similar pattern of abundance of β-cell, α-cell and δ-cell population was determined by flow cytometry analysis (37.52 ± 9.74%, 31.72 ± 5.67%, and 2.73 ± 2.73% respectively). Flow cytometry findings of the endocrine cell population within caprine islets were consistent with the microscopic investigation results. The morphological study of caprine islet revealed arrangement of the different islet cell types, which can lead to better understanding of different cell type interactions in caprine islets. The cytoarchitectural study of caprine islet can be occasioned to the comparison of similarity and dissimilarity of caprine islet cytoarchitectural features with other species islets and their physiological structures. However, anatomical study of caprine islet was conducted to in vitro and in vivo function assessment. Two agents of antioxidant and secretagogue were considered to enhance viability and functionality of caprine islets. Tocopherol as an antioxidant agent could offer antiapoptosis reaction and secretagogue agent, 3-isobutyl-1-methylxanthine (IBMX), enhance insulin secretion of caprine islets in the culture. The impact of supplementing antioxidant (tocopherol) and secretagogue factors (IBMX) on caprine islet viability during a short period maintenance of caprine islet culture was also assessed. The treated caprine islets with mentioned agents showed stability of islet morphology in cell culture, viability and functionality due to microscopy observation, FDA/PI staining and insulin secretion while stimulated by a high and low glucose stimulation, respectively (Day 1; 0.24 ± 0.09 μg/L, 0.13 ± 0.02 μg/L, Day 3; 0.19 ± 0.07 μg/L, 0.07 ± 0.02 μg/L, Day 5; 0.22 ± 0.05 μg/L, 0.11 ± 0.02 μg/L). These results can be promoted via molecular and gene expression studies on caprine islet. The insulin promoter gene (PDX1) as one of the most important genes in pancreas and islet was studied in caprine islets. Because it plays essential roles in pancreas and islet expansion, pancreas growth, islet formation within the pancreas and insulin secretion from β-cells. The PDX-1 and its protein expression were simultaneously assessed in the supplemented caprine islet culture. The results showed PDX1 gene up-regulation during five days of tocopherol and 3-isobutyl-1-methylxanthine supplemented caprine islet culture compared with the control group, serum-free media, with the relative quantification (RQ) value, day 1; 7.85 ± 1.20, day 3; 1.84 ± 0.14, and day 5; 6.80 ± 2.08 fold. Enhancement of PDX-1 expression in caprine islet results to produce more effective islets for in vivo study and xenotransplantation approach. The final aim of this study was to assess caprine islet functionality after xenotransplantation into a diabetic murine model. The optimal islets (size range between 50-250 μm) of viable purified caprine islets were transplanted into the recipient group (immunosuppressed diabetic mice) and compared with control groups of nondiabetic mice, un-grafted diabetic mice without immunosupresive drug injection, immunosuppressed mice with sham graft and islets grafted mice without immunosuppressive drug injection. Glucose tolerance test, blood glucose monitoring and microscopic examination of transplanted graft collectively indicated a reversion of diabetic status in STZ induced immunosuppressed mice. Non-fasting blood glucose level, 8.04 ± 0.44 mM/L, decreased from 23.3 ± 5.4 mM/L, meanwhile serum insulin level increase from 0.01 ± 0.001 μg/L to 0.56 ± 0.17 μg/ L and recipient mice body weights increased from 23.64 ± 0.31g to 25.85 ± 0.34 g (p < 0.05). In conclusion, the combination of tocopherol and IBMX was capable to impair the rate of apoptosis, improve the viability of caprine islets for short period culture and enhance the duodenal homeobox gene and protein expression. It might be considered a potential treatment to improve islet viability in vitro before islet transplantation. As the first attempt of using purified caprine islets, results indicate that the grafted islets were capable to retrieval diabetes in immunosuppressed STZ-injected mice.